2014
DOI: 10.1111/nph.12867
|View full text |Cite
|
Sign up to set email alerts
|

S‐acylation anchors remorin proteins to the plasma membrane but does not primarily determine their localization in membrane microdomains

Abstract: Summary Remorins are well‐established marker proteins for plasma membrane microdomains. They specifically localize to the inner membrane leaflet despite an overall hydrophilic amino acid composition. Here, we determined amino acids and post‐translational lipidations that are required for membrane association of remorin proteins. We used a combination of cell biological and biochemical approaches to localize remorin proteins and truncated variants of those in living cells and determined S‐acylation on defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 54 publications
(108 reference statements)
3
78
0
Order By: Relevance
“…The study of Jarsch et al (2014), which described various different localisation patterns for the REM protein family in plant PMs, revealed that the clusters of these PM-associated proteins also hardly undergo lateral movements. Since REMs bind to the inner leaflet of PMs (Konrad et al, 2014) and therefore cannot directly interact with the extracellular cell wall, a restrictive influence of the cortical cytoskeleton on the lateral PM mobility should not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Jarsch et al (2014), which described various different localisation patterns for the REM protein family in plant PMs, revealed that the clusters of these PM-associated proteins also hardly undergo lateral movements. Since REMs bind to the inner leaflet of PMs (Konrad et al, 2014) and therefore cannot directly interact with the extracellular cell wall, a restrictive influence of the cortical cytoskeleton on the lateral PM mobility should not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…A C-terminal 109 nucleotide sequence of MtSYMREM1 (ref. 66), covering the C-terminal remorin anchor, was amplified from pDONR207-MtSYMREM1 with the primers FV03 (5′-GGG GAATTC TGGGGAAGAAATCCTCAAGGTAGAG-3′) and FV04 (5′-CCCC GGATCC CTAACTGAAAAACCTTAAACCGCTG-3′). The resulting PCR product was cloned into pENTR-tagRFP-T using the introduced EcoRI and BamHI restriction sites (underlined) to obtain pENTR-tagRFP-T-REM.…”
Section: Methodsmentioning
confidence: 99%
“…Although, individual knockout mutant of LIP1 and LIP2 did not have any defects the double mutant can cause sterility due to loss of pollen tube guidance (Liu et al, 2013). S-acylation of remorin proteins, a group of well-known plasma membrane marker proteins, contribute to their subcellular localization (Konrad et al, 2014). Very recently, Kumar and his coworkers confirmed that a number of the catalytic subunits of cellulose synthase complex (CSC) in Arabidopsis are S-acylated.…”
Section: S-acylationmentioning
confidence: 99%